PENGARUH PERSEPSI PENGETAHUAN, INFORMASI, DAN RELIGIUSITAS TERHADAP MINAT BERWAKAF UANG - Pramudia, Rizkie Anugerah; Syarief, Mochamad Edman (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
This study aims to determine the perception of the Muslim community in West Java on cash waqf. The variables used in this study were knowledge, information and religiosity variables. This research is a quantitative study using Structural Equation Model-Partial Least Square (SEM-PLS) with the WarpPLS tool. The results showed that the variables of knowledge, information and religiosity had a positive effect on the interest to donating cash waqf. Positive public perceptions of cash waqf need to be supported by more massive socialization and education. Obviously, proper regulations also need to be prepared so that the purpose of cash waqf is achieved